Makna Filosofis Motif Kikit pada Tenun Ikat Marobo di Desa Umakatahan Kecamatan Malaka Tengah, Kabupaten Malaka - Fermelia Renaldis Bria; Antonius Bere; Clotilde Seran; Augusta De Jesus Magalhaes (International Forum of Researchers and Lecturers, 2026)
Marobo ikat weaving is one of the cultural products of the Malaka Regency community that contains aesthetic, social, and philosophical values. One of the decorative motifs found in the weaving is the Kikit motif. In the local language, Kikit refers to an eagle or garuda. This study aims to describe the form and reveal the philosophical meaning of the Kikit motif in Marobo ikat weaving in Umakatahan Village, Malaka Tengah District, Malaka Regency. The study used a qualitative approach with a descriptive method. Data were collected through interviews with weavers, traditional leaders, and residents who know the history and meaning of the Kikit motif. Supporting data were obtained through observations of the fabric and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The validity of the data was checked through source triangulation. The results of the study indicate that the Kikit motif is a depiction of an eagle or garuda that has a strong character, is able to fly high, move agilely, and catch targets accurately. The motif contains philosophical meanings in the form of gallantry, courage, strength, dexterity, determination, authority, and high ideals. The Kikit motif also serves as a cultural identity, a medium for conveying life values, and a link between the current generation and ancestral heritage. Therefore, the Kikit motif needs to be preserved through family education, documentation, weaving training, and the use of weaving that respects the cultural values ​​of the Malacca people.